Do Violence Acceptance and Bystander Actions Explain the Effects of Green Dot on Reducing Violence Perpetration in High Schools?. Issue 21 (November 2021) - Bush, Heather M.; Coker, Ann L.; DeGue, Sarah; Clear, Emily R.; Brancato, Candace J.; Fisher, Bonnie S.
This study extends prior analyses from a 5-year multisite cluster-randomized controlled trial to examine how the previously reported effects of the Green Dot bystander-based prevention program worked to reduce violence perpetration. Bystander-based interventions are hypothesized to prevent violence by reducing violence acceptance and increasing trained participants' willingness and ability to actively engage others in violence prevention using safe and effective bystander actions to diffuse or avoid potentially violent situations. We tested this hypothesis by examining whether Green Dot worked to reduce violence through two mediators measured over time: reducing violence acceptance and increasing bystander actions. When accounting for changes in these mediators over time, the effect of this intervention on violence perpetration was hypothesized to be attenuated or explained. At baseline (spring 2010) and annually (2011-2014), all students in recruited high schools (13 intervention, 13 control) completed an anonymous survey (response rate = 83.9%). Student responses were aggregated as school-level counts for the analysis. Path analyses estimated direct and indirect effects at specific points in the implementation of the intervention. Longitudinal models were used to determine if changes in violence acceptance and bystander actions could explain or attenuate the effect of the intervention. Time-framed path model analyses indicated that the intervention worked as expected to increase bystander behaviors and reduce violence acceptance; both potential mediators were significantly associated with sexual violence perpetration. In addition, after adjusting intent-to-treat models for the hypothesized mediators, the intervention was no longer associated with violence perpetration. In conclusion, these findings indicate that this bystander intervention worked as hypothesized to reduce sexual violence perpetration by creating theory-based changes in students' violence acceptance and bystander actions.